Vasodilatory Effect of Guanxinning Tablet on Rabbit Thoracic Aorta is Modulated by Both Endothelium-Dependent and -Independent Mechanism - Ling, Yun; Shi, Jiajun; Ma, Quanxin; Yang, Qinqin; Rong, Yili; He, Jiangmin; Chen, Minli (Frontiers in Pharmacology, 2021)
Vasodilatory therapy plays an important role in the treatment of cardiovascular diseases, especially hypertension and coronary heart disease. Previous research found that Guanxinning tablet (GXNT), a traditional Chinese compound preparation composed of Salvia miltiorrhiza (Danshen) and Ligusticum chuanxiong (Chuanxiong), increase blood flow in arteries but whether vasodilation plays a role in this effect remains unclear. Here, we found that GXNT significantly alleviated the vasoconstriction of isolated rabbit thoracic aorta induced by phenylephrine (PE), norepinephrine (NE) and KCl in a dose-dependent manner with or without endothelial cells (ECs). Changes in calcium ion levels in vascular smooth muscle cells (VSMCs) showed that both intracellular calcium release and extracellular calcium influx through receptor-dependent calcium channel (ROC) declined with GXNT treatment. Experiments to examine potassium channels suggested that endothelium-denuded vessels were also regulated by calcium-activated potassium channels (Kca) and ATP-related potassium channels (KATP) but not voltage-gated potassium channels (kV) and inward rectifying potassium channels (KIR). For endothelium-intact vessels, the nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) contents in vascular tissue obviously increased after GXNT treatment, and pretreatment with the NO synthase inhibitor Nw-nitro-L-arginine methyl ester(L-NAME) or guanylyl cyclase inhibitor methylthionine chloride (MB) significantly inhibited vasodilation. An assessment of NO-related pathway protein expression revealed that GXNT enhanced the expression of phosphorylated endothelial NO synthase (eNOS) in a dose-dependent manner but had no effect on total eNOS, p-Akt, Akt or PI3K levels in human umbilical vein ECs (HUVECs). In addition to PI3K/AKT signaling, Ca2+/calmodulin (CaM)-Ca2+/CaM-dependent protein kinase II (CaMKII) signaling is a major signal transduction pathway involved in eNOS activation in ECs. Further results showed that free calcium ion levels were decreased in HUVECs with GXNT treatment, accompanied by an increase in p-CaMKII expression, implying an increase in the Ca2+/CaM-Ca2+/CaMKII cascade. Taken together, these findings suggest that the GXNT may have exerted their vasodilative effect by activating the endothelial CaMKII/eNOS signaling pathway in endothelium-intact rings and calcium-related ion channels in endothelium-denuded vessels.